B2B digital marketing strategy: A framework for assessing digital touchpoints and increasing customer loyalty - Elina Bakhtieva (Institute of Economic Research (IER), 2017)
Digital marketing has changed the nature of company-to-customer communication. With rising information overload and reduced decision-making time, touchpoints have gained additional importance by yielding customer loyalty. Yet the existing digital marketing tools have failed to keep pace with these trends. Companies are lacking a simple framework that focuses on a digital marketing strategy built around touchpoints and customer loyalty. This is especially relevant for B2B companies, which due to their specifics are more dependent on customers and less flexible in adapting of new digital trends. A B2B business strategy tailored to digital trends demands a re-evaluation of prior understanding of a product portfolio, a company's internal and external environment. The purpose of the article is to present a framework that helps to undertake the necessary changes and enables the connections with industry. The suggested model has been drawn from the literature review and been extended based on the findings of an empirical multiple case study. Aspiring to follow trends in digital marketing and to help B2B companies to adapt their strategy to ongoing changes in company-to-customer communication, a new framework has been developed. The framework aims to increase customer loyalty and focuses on channels/touchpoints, assets, skills, audience and customer journey. The model could be beneficial for Chief Marketing Officers (CMO) and other C-levels by offering a simple and reliable tool for improving a company's position in the digital marketplace. Moreover, it enables continuously adjustment of an already existing business strategy.
Keywords: M31; L1; 330; digital marketing; customer loyalty; touchpoints; B2B digital marketing strategy; B2B industrial companies